Statistical analysis of the impact of “terms of trade” on the trade balance of Ukraine - Nepran, A. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
The article reveals the impact of the “terms of trade” on the state of Ukraine’s trade balance.  The purpose of the article is to quantitatively assess the impact of the "terms" of foreign trade on the state of the trade balance and on the main export goods of the Ukrainian economy and to develop proposals for eliminating negative consequences. The methodological basis of the study is the determined indices of price and quantitative terms of foreign trade for 2019–2023. A number of important trends in foreign trade have been identified: a negative balance in foreign trade in goods, a fall in prices for leading raw materials of Ukrainian exports. The volumes of losses of trade income from the price factor have been established both for the economy as a whole and for individual commodity groups. Based on the calculations, the conclusion is drawn that the deterioration of the terms of trade has caused a decrease in the purchasing power of exports and significant losses of income of national producers from foreign trade in goods. It is proven that as a result of the deterioration of the terms of trade, the losses of trade income of the Ukrainian economy exceeded 18 billion USD. A quantitative assessment of the impact of changes in the terms of trade indicates chronic deficits in Ukraine's trade balances, which are the result of increased instability of raw material commodity markets, a relative decline in the importance of trade in raw materials, deterioration of the terms of trade and an increase in the scale of exchange inequivalence. It was established that the scale of the fall in prices for raw materials from Ukraine was so great that the losses from them were not covered by the increase in the physical volume of trade. The losses were especially significant for the main export commodities of raw material value and goods with a low degree of processing. As shown by the calculations, for grain crops, financial losses from the deterioration of the terms of trade in 2023 amounted to 2891.1 million USD, for oilseeds and ferrous metals ― 1026.6 and 386.0 million USD, respectively. An assessment of the scale of losses of the Ukrainian economy from the price factor confirms the unfoundedness of further increasing the physical volume of exports of raw materials and goods with a low level of processing. This requires a reorientation of the foreign trade strategy towards abandoning the increase in exports of raw materials, which leads to significant losses of trade income and poses a threat to the stability and economic development of the country.